Senam Sehat Anak Indonesia Improve Peak Expiratory Flow Rate in Children with Obesity - Ramadhania, Farah Alya; Asmara Putri, Rahmi Isma; Setiawati, Erna; Nency, Yetty Movieta (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2020)
Introduction: Excessive fat accumulation in the obese child causes complex problems in the respiratory system. Respiratory system function can be improved by exercise. One exercise model that is suitable for children is Senam Sehat Anak Indonesia (SSAI). The quality of the respiratory function system is measured using Peak Expiratory Flow Rate (PEFR).Objective: to validate the PEFR’s differences in obese children before and after performing SSAI.Methods: This research using one group pre-posttest experimental design with total sample of 20 obese children using purposive sampling method. The research instrument uses weight scale, height scale, and peak flow meter. SSAI was given to all subjects twice a week for six weeks. Paired T Test statistical analysis was used to examine the PEFR’s differences before and after performing SSAI, considered significant if p<0.05.Results: The PEFR’s mean of all subjects before performing SSAI was 258.25 ± 39.51 L∕minute, while PEFR’s mean after performing SSAI twice a week for 6 weeks was 282.50 ± 43.03 L∕minute, (p=0,000).Conclusion: The PEFR’s mean of obese children was increase significantly after performing SSAI twice a week for 6 weeks